Sound absorption and morphology characteristic of porous concrete paving blocks at different sizes of coarse aggregate - Putra Jaya, Ramadhansyah (2015)
In this study, sound absorption and morphology characteristic of Porous Concrete Paving Blocks (PCPB) at different sizes of coarse aggregate were presented. Three different sizes of coarse aggregate were used; passing 10 mm retained 5 mm (as Control), passing 8 mm retained 5 mm (8 – 5) and passing 10 mm retained 8 mm (10 – 8). The sound absorption test was conducted through the impedance tube at different frequency. It was found that the size of coarse aggregate affects the level of absorption of the specimens. It also shows that PCPB 10 – 8 resulted in high sound absorption compared to the other blocks. On the other hand, microstructure morphology of PCPB shows a clearer version of existing microcracks and voids inside the specimens which affecting the results of sound absorption.